A Framework for Organizational Effectiveness in the Non-Profit Organization - Lim, Jason Koon Seng (2008)
None profit organizations are entrusted with societys most important functions educating minds, uplifting souls and protecting health and safety. Most research on management performance systems has focused on for profit organizations with less emphasis or research conducted in the none profit sector. Lately, however, the publics faith in these institutions has been seriously undermined by revelations of wrongdoing and mismanagement. Recent scandals in organizations such as United Way of America, the United Nations, Empire Blue Cross and the National Association for the Advancement of Colored People bring to light that the performance of none profits is shrouded behind a veil of secrecy lifted only when disasters occur. (Herzlinger, 1999) According to Herzlinger, four common problems manifest themselves in none profit organizations, which are being aggressively tackled in profit organizations. First is the problem of ineffective organizations, ones that do not accomplish their social missions. A second problem is inefficiency such as spending too much on fund raising and administration and devoting less than a majority of funds to a service. A third difficulty is that of private inurement, where individuals who control tax exempt organizations attain excessive benefits for themselves. A fourth problem is excessive risk and lack of accountability. These problems are readily associated with none profit organizations as they lack the self interest that comes with ownership ensuring managers do not receive excessive compensation, that the business accomplishes it goals efficiently, and that risks are appropriately evaluated. Second they often lack the competition that would force efficiency and finally they lack the ultimate barometer of business success, the profit measure. (1999)